A low molecular weight brown algae Laminaria japonica glycan modulation of gut microbiota and body weight in mice. Issue 24 (25th November 2021) - Jin, Zhen; Fang, Zhifeng; Pei, Zhangming; Wang, Hongchao; Zhu, Jinlin; Lee, Yuan-kun; Zhang, Hao; Zhao, Jianxin; Lu, Wenwei; Chen, Wei
Abstract : Brown algae glycan from Laminaria japonica (LJNP) is a heterogeneous glycan composed of glucose and fucose, which drove Bacteroides vulgatus and Bacteroides uniformis to regulate amino acid metabolism and glycometabolism. Abstract : Brown algae glycan from Laminaria japonica (LJNP) is a heterogeneous glycan with two apparent molecular weights of 1.1 and 37.3 kDa, and is mainly composed of α β-glucan and a few fucosyl residues. To explore the regulation of gut microbiota and the host, LJNP and 2′-fucosyllactose (2′FL) were compared to investigate their effect on mice via oral administration. Using metagenomic and metabolomic analyses, we found that 2′FL mainly relied on Adlercreutzia equolifaciens and Akkermansia muciniphila to improve gut amino acid and bile acid metabolism, whereas LJNP mainly drove Bacteroides vulgatus and Bacteroides uniformis to regulate gut amino acid metabolism and glycometabolism. Moreover, LJNP showed a weight loss effect and better protection of the intestinal barrier than 2′FL. We further employed LJNP and 2′FL on a germ-free mice model. Interestingly, the body weight management was not microbiome mediated. This study showed that LJNP can ameliorate the intestinal barrier through modulation of the gut microbiota, maintain the blood glucose level, and regulate body weight and the antioxidant function. Although the benefits of LJNP on host health were partly revealed, mechanisms such as the weight loss effect require further study.